ANALISIS KONTEN MEDIA SOSIAL DALAM PERSPEKTIF BAHASA INDONESIA DAN PENDIDIKAN AGAMA ISLAM - Anny Wahyu Di Jayanti; Muhammad Abdul Ilah (JBI : Jurnal Bahasa Indonesia, 2025)
This study aims to analyze social media content related to the use of language and the educational value of Islamic religion. The background of this research is based on the rapid development of social media as a medium of communication that affects the way religious values are conveyed, especially among the younger generation. The method used is quantitative content analysis by collecting data from various social media platforms, then the data is analyzed based on the frequency of occurrence of language themes and religious values. The results of the study show that there are five dominant themes, namely the use of casual language, traditional religious terms, modern slang, moral messages, and easy-to-understand religious teachings. These findings indicate that religious content on social media combines language innovation and tradition preservation to effectively convey messages. In conclusion, the research emphasizes the importance of adapting language styles in religious digital communication so that moral messages and religious teachings can be more easily accepted and understood by today's audience. This research contributes to the understanding of digital religious communication and offers practical recommendations for religious content creators.